Women's information needs about ductal carcinoma in situ before mammographic screening and after diagnosis: a qualitative study. - Prinjha, S; Evans, J; McPherson, A (2006)
OBJECTIVES: To explore the attitudes of women with screen-detected ductal carcinoma in situ (DCIS) towards information provision for mammographic screening. SETTING: Respondents recruited throughout the UK during 2003-2004. METHODS: Qualitative study using semi-structured interviews. PARTICIPANTS: Ten women diagnosed with DCIS as a result of mammographic screening. RESULTS: None of the women with DCIS had heard of it before their diagnosis. Most would have liked more information about DCIS when invited for routine screening. Comprehensive information about the benefits and risks of mammographic screening, including the possibility of a DCIS diagnosis, would have enabled them to make a fully informed choice about attending for screening. CONCLUSION: DCIS is an inescapable outcome of mammographic screening and, until it is better understood, the screening industry needs to inform women about its existence and the lack of understanding of its natural history and management. Being alerted before screening to the possibility of a DCIS diagnosis and the uncertainty associated with it would better enable women to make fully informed decisions about whether to attend and could help to alleviate some of the distress women currently feel when diagnosed with DCIS.